Constructing a Theological-Philosophical Framework for Climate Justice: The Role of Religious Education in Empowering Eco-ethical Action - Yosep Heristyo Endro Baruno; Nathan Sayono; Naufal Naufal; Meenu Sharma (Green Philosophy: International Journal of Religious Education and Philosophy, 2024)
This study proposes an integrative framework for climate justice that combines moral theology, ethical philosophy, and religious pedagogy to encourage active participation in eco-ethical actions. The framework addresses the growing need for religious communities to engage in environmental stewardship by merging traditional religious teachings with contemporary environmental ethics. The research emphasizes the importance of eco-ethical education within religious settings, which fosters a deep sense of moral responsibility toward environmental care. Data for the study was gathered through field observations and interviews with religious educators and environmental activists, aiming to understand current educational practices and to explore opportunities for integrating climate justice into religious curricula. The study found that, while there are challenges such as curriculum limitations, ideological resistance, and insufficient understanding of climate justice, the proposed framework offers a powerful tool for religious institutions to foster environmentally responsible and ethically committed individuals. It also highlights the potential for collaboration between religious organizations and environmental groups to further promote climate justice. The study concludes that religious education has a unique role in shaping individuals' attitudes towards environmental issues, offering a distinct advantage over secular approaches by embedding moral responsibility into faith-based practices. Further research is recommended to explore the integration of climate justice in religious education and its impact on community behavior and sustainability.